Department of Nutrition Physiology Institute of Sport Warsaw - Malczewska, J.
Equipment: Spectrophotometer SEMCO S91E; Body Impedance Analyser BIA 101/S. Research methods: Enzymatic determination of vitamins B1, B2, B6; total iron and total iron binding capacity; ferritin and transferrin receptor (by ELISA); haptoglobins (by radial immunodiffusion); assessment of food intake by 24 h dietary recalls; computer analysis of diet composition. Principal subject: Iron metabolism and nutrition status in athletes. Current research: Transferrin receptor/ferritin index (sTfR/log ferr) as an indicator of iron stores in competitive athletes. Body components of male and female athletes representing various sports (comparison of bioelectric impedance analysis and skinfolds method). Research achievements: Based o sTfR/log ferr index as the criterion of latent iron deficiency significantly higher incidence of iron deficiency was observed in women (26%) than in man (11%). Applied research: The sTfR/log ferr index is a better tool for detecting iron deficiency in athletes than either ferrine of soluble transferrin receptor (sTfR) alone, especially in iron deficient erythropoiesis despite a high, exercise - induced variability of ferritin concentration. Sports studied: Judo, wrestling, boxing, pentathlon, archery, orienteering, gymnastics, speed skating, kayaking, rowing, basketball, handball, volleyball.